Demographic variations in maxillary pathologic lesions - an institutional study - GAUR, SHIVANGI; MADHULAXMI M,; HEMAVATHY O R, (The journal of contemporary issues in business and government, 2020)
A variety of benign and malignant lesions involve the maxilla and maxillary sinus. The presenting features, symptomatology and advanced diagnostic imaging techniques help in achieving a differential diagnosis however histopathological examination remains the mainstay of definitive diagnosis. This study aims to identify the frequency of isolated maxillary pathologic lesions (benign and malignant) and its gender and age distribution. After clearance from the institutional ethical committee, a retrospective study was performed for a period of ten months from June 2019 to March 2020 in our institution. 90 cases of pathology were reviewed out of which 29 were included in the study based on the inclusion criteria. 68.97% males and 31.03% females reported with pathologic lesions of the maxilla alone in our center. Malignant maxillary lesions show the highest frequency of occurrence in 17.24% in the 41-60 age group (p value-0.233). Treatment modalities used for various lesions diagnosed in the maxilla showed the highest degree of association with surgical excision being the most commonly performed for malignant lesions and enucleation for cysts and benign tumors (p value- 0.000). Maxillary benign pathological lesions have a tendency to mimic malignant lesions. Hence it is important to document and identify lesions most commonly encountered in a particular population to provide for adequate and appropriate treatment care needs.